Discrimination unveiled: a field experiment on the barriers faced by Muslim women in Germany, the Netherlands, and Spain - Fernández-Reino, M; Di Stasio, V; Veit, S (Oxford University Press, 2022)
We examine the penalties faced by veiled and unveiled Muslim women when applying for jobs in three European labour markets: Germany, the Netherlands, and Spain. We rely on recent literature comparing public opposition towards Muslims in general and opposition to Muslims’ religious practices, such as the wearing of the hijab. Based on a cross-nationally harmonized field experiment on hiring discrimination, we use two different signals of Muslimness (volunteering activities in a Muslim community centre or wearing the Muslim headscarf) to identify whether employers discriminate against Muslims as a group or against Muslims adhering to specific Muslim practices—in this case, wearing the headscarf. We present robust evidence that veiled Muslim women are discriminated against in Germany and the Netherlands, but only when applying for jobs that require a high level of customer contact. In Spain, however, the level of discrimination against veiled Muslim women is much smaller than in the other two countries. The high level of discrimination we found in the Netherlands, where the institutional context has traditionally been open to the accommodation of religious minority rights, is particularly surprising and points to the possibly stigmatizing effect of recent policies geared towards the cultural assimilation of immigrants.